A NOVEL LAYER BY LAYER ANGLE BASED FLOODING PROTOCOL FOR UNDERWATER WIRELESS SENSOR NETWORKS - ,, TARIQ ALI (2014)
This research presents the problem of data routing tn volatile underwater environment, where providing better communication and maximizing the communication performance of the network is always a challenging task. Following are the main issues possess by the environment, radio signals cannot properly propagate underwater, so there is a need for acoustic technology that can support better data rates and reliable underwater wireless communications. Secondly, node mobility, 3-0 spaces and horizontal communication links between the nodes are some critical challenges to the researcher in designing new routing protocols for UWSNs. Many algorithms have been proposed to overcome the problem of large propagation delays and unreliable link quality. Some of them provide better solution for these issues, yet horizontal communication links between the nodes and unexpected movements of nodes still need attention.